2022
DOI: 10.1186/s43055-022-00882-1
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave elastography as a quantitative method for thyroid gland elasticity assessment in pediatrics patients with autoimmune-related thyroid disease, diagnostic utility and laboratory correlation

Abstract: Background Autoimmune thyroiditis (AIT) is the most common thyroid pathology in pediatric patients among which Hashimoto’s thyroiditis has the highest prevalence. Along with size, measuring mechano-acoustic tissue elasticity is evolving as an important parameter in the evaluation of diffuse thyroid pathology. This study aims to investigate the role of shear wave elastography (SWE) in the diagnosis of autoimmune thyroid disease (AITD) in the pediatric population and also compare the elasticity b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…While some studies have found a mild correlation between EI and ATG and a moderate correlation with ATPO [37], others have found no correlation between EI and antibody levels [41,42]. In addition, Kamel et al found correlations between elasticity and antibody levels to be statistically insignificant (p > 0.05) [39]. Kandemirli et al found a moderate correlation between elasticity and ATPO, but a non-significant correlation between EI and ATG (p > 0.05) [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies have found a mild correlation between EI and ATG and a moderate correlation with ATPO [37], others have found no correlation between EI and antibody levels [41,42]. In addition, Kamel et al found correlations between elasticity and antibody levels to be statistically insignificant (p > 0.05) [39]. Kandemirli et al found a moderate correlation between elasticity and ATPO, but a non-significant correlation between EI and ATG (p > 0.05) [36].…”
Section: Discussionmentioning
confidence: 99%
“…Patients diagnosed with CAT had elasticity values that were considerably greater (35.6 kPa, with an interquartile range of 8.43-103.7 kPa) than the control group (9.35 kPa, with an interquartile range of 5.73-13.21 kPa). The threshold value for elasticity was determined to be 12.317 kPa, and the sensitivity and specificity of the test were 96.9% and 100%, respectively [39].…”
Section: Discussionmentioning
confidence: 99%
“…Kamel et al [ 43 ], in their study evaluating thyroid gland elasticity in pediatric patients with autoimmune thyroid disease, found thyroid SWE values to be significantly higher in children with autoimmune thyroiditis compared to healthy children due to parenchymal stiffness caused by lymphocytic infiltration and interstitial fibrosis. In the literature, a proportionally higher increase in tissue stiffness values has been found in autoimmune thyroiditis.…”
Section: Discussionmentioning
confidence: 99%
“…Extrapolating the excellent results observed in the diffuse chronic liver disease, elastography was used in the differential diagnosis of DTD from normal thyroid. Both strain and 2D-shear wave elastography (2D-SWE) demonstrated increased stiffness in autoimmune thyroid disease compared with normal thyroid ( 35 , 36 ), both in adult ( 37 ) and pediatric populations ( 38 , 39 ).…”
Section: Introductionmentioning
confidence: 99%